Comparison of Post-operative Outcomes Between Direct Axillary Artery Cannulation and Side-Graft Axillary Artery Cannulation in Cardiac Surgery: A Systematic Review and Meta-Analysis - Xie, Yi; Liu, Yu; Yang, Peng; Lu, Chen; Hu, Jia (Frontiers in Cardiovascular Medicine, 2022)
Background There is a growing perception of using axillary artery cannulation to improve operative outcomes in cardiopulmonary bypass surgery. Two techniques, direct cannulation or side-graft cannulation, can be used for axillary artery cannulation, but which technique is better is controversial. Methods A meta-analysis of comparative studies reporting operative outcomes using direct cannulation vs. side-graft cannulation was performed. We searched the PubMed, EMbase, Web of Science, and Cochrane Library. Outcomes of interest were neurological dysfunction, cannulation-related complications and early mortality. The fixed effects model was used. Results A total of 1,543 patients were included in the final analysis. Direct cannulation was used in 846 patients, and side-graft cannulation was used in 697 patients. Meta-analysis showed a higher occurrence of neurological Complication in direct cannulation group [odds ratio, 1.45, 95% CI (1.00, 2.10), χ2 = 4.40, P = 0.05] and a significantly higher incidence of cannulation-related complications in the direct cannulation group [odds ratio, 3.12, 95% CI (1.87, 5.18), χ2 = 2.54, P < 0.0001]. The incidence of early mortality did not have a difference [odds ratio, 0.95, 95% CI (0.64, 1.41), χ2 = 6.35, P = 0.79]. Conclusions This study suggests that side-graft axillary artery cannulation is a better strategy as it reduces the incidence of neurological dysfunction and cannulation-related complications. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022325456.